Behaviour of steel structures with base isolator under low intensity earthquake effect - 450768 Jati Sunaryati; Marzuki Khalid, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Doktor Falsafah (Fakulti Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2008